Knowledge, Attitude, and Practice Towards Thalassemia Prevention among College Students in Universitas Padjadjaran, Bandung, Indonesia - Kusumadewi, Ratu Istihajar; Tansah, Haryono; Widjadjakusumah, Anggraini (Althea Medical Journal, 2023)
Background: Thalassemia is the most common hereditary anemia disease. Sixty thousand thalassemia major patients are born each year and require continuous blood transfusion to survive, meanwhile 12% die in the perinatal period due to anaemic conditions. Specifically in Indonesia, 10% of the societies are deemed to be carriers, but the studies on thalassemia prevention are still limited.. This study aimed to explore the correlations between knowledge, attitude, and practice (KAP) of college students toward thalassemia prevention.Methods: This study was a cross-sectional analytic study conducted in September−October 2015. A total of 536 respondents from various faculties in Universitas Padjadjaran were gathered based on purposive sampling. The data obtained from validated questionnaires were analyzed by Spearman’s Rank correlation test.Results: The correlation between knowledge and attitude was weak, but the p-value was significant (rs= +0.388, ρ= 0.041). Yet, there was no correlation between knowledge and practice (rs= +0.280, ρ= 0.063), nor between attitude and practice (rs = +0.012, ρ= 0.786).Conclusions: Knowledge positively affects college students’ attitude to thalassemia prevention; however, it does not have the same effect on its practice. It is consistent with the attitude, which also does not correlate with the practice of college students toward thalassemia prevention. Therefore, other affirmative actions or direct interventions and programs are still needed to maximize  thalassemia prevention.